2016 XXII International Conference on Electrical Machines (ICEM) 2016
DOI: 10.1109/icelmach.2016.7732908
|View full text |Cite
|
Sign up to set email alerts
|

Thermal management of a high speed permanent magnet machine for an aeroengine

Abstract: --The paper describes the mechanical and thermal design of a high speed, high power density synchronous permanent magnet machine for an aero engine starter generator system with a power rating of 150 kW and maximum speed of 32,000 rpm. As both mechanical and thermal aspects have a direct impact on machine overall performance and weight reduction, a critical design optimisation was carried out. Intensive cooling is guaranteed by direct liquid oil-cooling of stationary components; a stator sleeve is also introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…5 (a). According to (11), increasing the electrical loading improves the magnetic body force, and hence the thermomagnetic effect. As a result, the temperature reduction using ferrofluid to replace nanofluid is increased from 13 ℃ to 31 ℃ when the the current density increases from 18.4A/mm 2 to 22.1A/mm 2 .…”
Section: A Single Layer Windingsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 (a). According to (11), increasing the electrical loading improves the magnetic body force, and hence the thermomagnetic effect. As a result, the temperature reduction using ferrofluid to replace nanofluid is increased from 13 ℃ to 31 ℃ when the the current density increases from 18.4A/mm 2 to 22.1A/mm 2 .…”
Section: A Single Layer Windingsmentioning
confidence: 99%
“…This is mainly due to the poor thermal conductivity of air in the end space and therefore a high thermal resistance between the end-windings and machine housing where cooling system such as water jacket is located. To improve the cooling of end-windings, ventilation cooling [8,9] and forced oil cooling [10,11] have been investigated. For these cooling technologies, inlets and outlets are introduced on the endcaps or machine housing to allow air or liquid to flow through the machine.…”
mentioning
confidence: 99%
“…The effective tool to modelling and design the interior cooling of the PMSM rotor is the MATLAB/Simscape software. [34][35][36] It can be observed that the temperature of the magnet decreases significantly as the rotor cooling is provided with respect to the PMSM operating point. The highest drop of the PMSM magnets temperature of 40K occurs at 10000 rpm in comparison with not cooled PMSM, as we see both the temperatures 140 and 100 coincide at 10000 rpm elsewhere they are two different lines (Figure 3).…”
Section: Effects Of Temperature Risementioning
confidence: 99%
“…The temperature of the winding decreased by about 50% and 38% compared with cooling by air and water jacket only, respectively. Rocca et al [61] presented research on thermal management of high-speed permanent magnet motor with oil cooling. A banding sleeve was used to avoid overly big windage in the air gap.…”
Section: The Thermal Management Of Permanent Magnet Motormentioning
confidence: 99%